KCa3.1 Channels Promote Cardiac Fibrosis Through Mediating Inflammation and Differentiation of Monocytes Into Myofibroblasts in Angiotensin II–Treated Rats. Issue 1 (8th January 2019) - She, Gang; Ren, Yu‐Jie; Wang, Yan; Hou, Meng‐Chen; Wang, Hui‐Fang; Gou, Wei; Lai, Bao‐Chang; Lei, Ting; Du, Xiao‐Jun; Deng, Xiu‐Ling
Abstract : Background: Cardiac fibrosis is a core pathological process associated with heart failure. The recruitment and differentiation of primitive fibroblast precursor cells of bone marrow origin play a critical role in pathological interstitial cardiac fibrosis. The KC a 3.1 channels are expressed in both ventricular fibroblasts and circulating mononuclear cells in rats and are upregulated by angiotensin II. We hypothesized that KC a 3.1 channels mediate the inflammatory microenvironment in the heart, promoting the infiltrated bone marrow–derived circulating mononuclear cells to differentiate into myofibroblasts, leading to myocardial fibrosis. Methods and Results: We established a cardiac fibrosis model in rats by infusing angiotensin II to evaluate the impact of the specific KC a 3.1 channel blocker TRAM‐34 on cardiac fibrosis. At the same time, mouse CD4 + T cells and rat circulating mononuclear cells were separated to investigate the underlying mechanism of the TRAM‐34 anti–cardiac fibrosis effect. TRAM‐34 significantly attenuated cardiac fibrosis and the inflammatory reaction and reduced the number of fibroblast precursor cells and myofibroblasts. Inhibition of KC a 3.1 channels suppressed angiotensin II–stimulated expression and secretion of interleukin‐4 and interleukin‐13 in CD4 + T cells and interleukin‐4– or interleukin‐13–induced differentiation of monocytes into fibrocytes. Conclusions: KC a 3.1 channels facilitate myocardial inflammation and the differentiation of bone marrow‐derived monocytes into myofibroblasts in cardiac fibrosis caused by angiotensin II infusion.